Removal of Tetrabromobisphenol A by adsorption on pinecone-derived activated charcoals: Synchrotron FTIR, kinetics and surface functionality analyses. (January 2018) - Shen, Jian; Huang, Gordon; An, Chunjiang; Xin, Xiaying; Huang, Charley; Rosendahl, Scott
Graphical abstract: Highlights: Tetrabromobisphenol A (TBBPA) adsorption on pinecone-derived charcoal was studied. Insights from synchrotron FTIR and adsorption kinetics studies were obtained. The adsorption process was influenced by surface properties of activated charcoal. The surface functional groups of activated charcoal played an important role. The results are helpful for exploring the treatment and transport of TBBPA. Abstract: This study explored the adsorption of Tetrabromobisphenol A (TBBPA) on pinecone-derived activated charcoal. The interactions between TBBPA and activated-charcoal surface, as well as the corresponding effects of functionality and adsorption capacities, were investigated through synchrotron FTIR, kinetics and surface functionality analyses. It was found that multiple acid functional groups and their interactive effects played important roles. The adsorption on activated charcoal from Yellow pinecone was favored by the surface with high polarity, low aromaticity, and low surface area. In comparison, adsorption on activated charcoal from Scot pinecone was favored by the surface with high aromaticity and high surface area. The adsorption capacity and removal efficiency were significantly dependent upon the contents of acid functional groups on charcoal surface. This study showed that the newly presented evidence of interactions between oxygen-containing functional groups and TBBPA will be helpful for exploring the treatment and transport of such a contaminant in the environment.